Immunization status of children 12-36 months age of migrant workers and factors associated with it in urban areas of Bangalore East - Shweta Neminath Kurkuri; Mangala Subramanian (Wolters Kluwer Medknow Publications, 2024)
Background: Immunization is a cost-effective weapon against vaccine preventable diseases. Children of migrant workers suffer from lack of immunization because of frequent shift of places, poor knowledge, and low socioeconomic status. To assess the immunization status of children 12-36 months of age of migrant workers and factors associated it. To identify the reasons for non-immunization or partial immunization among these children. Material and Methods: A cross-sectional study was conducted among 500 migrant workers' children aged 12-36 months residing in Urban Bangalore east from February 2019 to August 2020. A cluster sampling method was incorporated. The data were collected using pre-tested semi-structured questionnaire. Data were analyzed using Epi-info™ Version 7.2.1 and SPSS version-21. Data were summarized in percentages, mean, standard deviation, and logistic regression. Results: The mean age of the children was 25.2340 ± 8.42 months. Out of 500 children, 88.60% were fully immunized, 11.40% were partially immunized, and no child was unimmunized. Significant predictors of immunization status of children were education of father and immunization card. Common reasons for dropout were inconvenient time (80.70%), unaware of need (77.19%), and busy schedule of parents (75.44%). The dropout rate of BCG to MR-1, Penta-1 to Penta-3, and Penta1to MR-1 was 6.49%, 0.85%, and 2.12%, respectively. Conclusions: Immunization coverage in the present study was 88.60%. Inconvenient time was the main reason behind partial immunization.